2021
DOI: 10.1155/2021/7016712
|View full text |Cite
|
Sign up to set email alerts
|

QTL Mapping of Traits Associated with Dual Resistance to the African Stem Borer (Busseola fusca) and Spotted Stem Borer (Chilo partellus) in Sorghum (Sorghum bicolor)

Abstract: Sorghum (Sorghum bicolor (L.) Moench) is an important food crop in semi-arid tropics. The crop grain yield ranges from 0.5 t/ha to 0.8 t/ha compared to potential yields of 10 t/ha. The African stem borer Busseola fusca Fuller (Noctuidae) and the spotted stem borer Chilo partellus Swinhoe (Crambidae), are among the most economically important insect pests of sorghum. The two borers can cause 15% - 80% grain yield loss in sorghum. Mapping of QTLs associated with resistance traits to the two stem borers is import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Insect resistance in field crops Ch Padmavathi and P G Padmaja and stem tunneling traits on two individual QTLs identified; thus, suggesting that the two traits can be improved using the same linked marker (Muturi et al, 2021).…”
Section: Wild Relatives As Sources Of Diverse Genes For Insect Resist...mentioning
confidence: 94%
“…Insect resistance in field crops Ch Padmavathi and P G Padmaja and stem tunneling traits on two individual QTLs identified; thus, suggesting that the two traits can be improved using the same linked marker (Muturi et al, 2021).…”
Section: Wild Relatives As Sources Of Diverse Genes For Insect Resist...mentioning
confidence: 94%
“…Furthermore, assessment of phenotypes led to the identification of two resistant lines for each QTL region present on chromosomes SBI-01, SBI-07, and SBI-10 in ICSB 29004 × Parbhani Moti (Gorthy et al 2017 ). In another study, a joint analysis for Busseola fusca and C. partellus revealed that marker CS132-2 was co-localized for leaf toughness and stem tunneling traits on two individual QTLs identified; thus, suggesting that the two traits can be improved using the same linked marker (Muturi et al 2021 ).…”
Section: Insect Resistance Qtls Identified In Major Field Cropsmentioning
confidence: 99%